Dynamic Organicism and the Traditional Imagination in Alobwed’Epie the Lady With a Beard - Ewane, George Ngide (Richtmann Publishing, 2011)
This paper sets out to examine the concept of dynamic organicism in the Bakossi traditional society as imaginatively revealedin Alobwed’Epie’s The Lady With A Beard. Dynamic organicism refers to an energetic and driving force instrumental in growth orchange; a universal literary phenomenon whereby the writer transcends the ordinary view of things, sees reality beyond the corporal frame ofexistence and through the imagination seeks an ideal and works towards changing the corrupt order of the universe by reinstating orderand moving it backwards to its natural state of felicity. The paper thus reads Alobwed ‘Epie’s The Lady With A Beard in the light ofromantic organicism. Emade suffers isolation because she realises that there exist reparations for her attempted breaking of the organicunit. Alobwed ‘Epie intimates that Emade’s ‘uppishness’ (sic) is the cause of her problems. It is only by reconciling with her communityand tradition that she will be able to live a peaceful life.